A Bibliometric Analysis of Challenges and Opportunities in Organic Agriculture Research for Environmental Sustainability and Public Health - Rahman Dani Lasamadi; Indra Rukmana (CV. HEI PUBLISHING INDONESIA, 2025)
Organic agriculture is increasingly recognized as a pivotal strategy for addressing environmental degradation and the public health risks associated with conventional farming practices. This bibliometric analysis maps the scientific landscape of organic agriculture research with an emphasis on environmental sustainability and human health. Using a dataset of more than 2,000 peer-reviewed articles indexed in the Web of Science over recent years, the study identifies an average annual publication growth rate of approximately 18.5%, indicating a rapidly expanding field of inquiry. The analysis reveals several key thematic clusters, including agronomic practices that enhance soil health and biodiversity; policy and market challenges related to certification and food security; and public health benefits associated with reduced pesticide exposure. Major contributions originate from the United States, China, and European countries, although significant geographical research gaps remain in developing regions. Overall, the findings underscore persistent challenges—such as scaling organic farming systems and harmonizing certification standards—alongside emerging opportunities in advanced agronomic innovation and long-term health outcome assessments. This study provides a strong evidence base to support policy development and to guide future research priorities within sustainable food system frameworks.